The Persuasive Techniques of Starbucks and Burger King Advertisements on Instagram Posts - Rizky Vita Losi; Takkas Josua Bernardo; Todo F. B. Sibuea; Rizki Ananda (ITScience (Information Technology and Science), 2022)
This study aimed to describe the persuasive techniques of Starbucks and Burger King advertisements on Instagram posts. The categories of persuasive techniques were referred to as Lamb's theory (2014). By using the descriptive qualitative method, the researchers collected one hundred data on Starbucks and Burger King advertisements on Instagram posts. Then, the data were analyzed by classifying and interpreting them into correct categories. The result of the study showed that: 1) Fifty data were taken from Starbucks advertisements on Instagram posts by the distribution as follows: 3 data of Alliteration, 3 data of Connotation, 6 data of Colloquial Language, 5 data of Evidence, 4 data of Hyperbole, 9 data of Inclusive Language, 6 data of Imagery, 4 data of Pun, 4 data of Repetition, 4 data of Rhetorical Question and 2 data of Simile, 2) Fifty data were taken from Burger King advertisements on Instagram posts by the distribution as follow: 4 data of Connotation, 4 data of Colloquial Language, 5 data of Evidence, 4 data of Hyperbole, 5 data of Inclusive Language, 6 data of Imagery, 2 data of Metaphor, 3 data of Pun, 5 data of Repetition, 10 data of Rhetorical Question and 2 data of Simile. Starbucks dominantly used Inclusive Language in their advertisements, while Burger King dominantly used Rhetorical questions in their advertisements. Both of them chose different persuasive techniques to represent their products.